Financial Literacy and Sustainable Entrepreneurial Competitiveness: North Meruya Community Service Implementation - Apriadi, Intan; Karyatun, Subur; Soelton, Mochamad; Thoullon, Muhammad Shirhan; Harisnanda, Adriatik; Sudiro, Achmad; Anah, Sri (Indonesian Journal of Society Development, 2024)
This community service aims to help the Financial Literacy Assistance Program to Create Entrepreneurial Competitiveness for Beginners and gain benefits from their presence in the family environment in utilizing used goods (trash). Micro, small and medium enterprises are an important element in supporting the national economy as a whole. Micro businesses are the driving force of the economic system in Indonesia which can survive during an economic crisis. This type of business helps the government in creating jobs and reducing poverty levels, through micro businesses creating new work units that use new workers who can support household income so that they remain productive in unstable economic times. Continuing the previous program, in 2024 Community Service activities will again be carried out for MSMEs in the North Meruya sub-district environment. This learning activity is related to mentoring MSME activists in North Meruya (also known as Meruya Ilir). North Meruya Village is one of the sub-districts located in Kembangan sub-district, West Jakarta City, Special Capital Region of Jakarta Province, Indonesia. One way to assist MSMEs is to provide education on financial literacy